Microscopic evaluation of cleaning efficiency of three different Nickel-Titanium rotary instruments - Maryam Bidar; Saeed Moradi; Maryam Forghani; Salma Bidad; Mahtab Azghadi; Shahrzad Rezvani; Shirin Khoynezhad (Iranian Endodontic Journal, 2010)
Introduction: This study compared the cleaning efficiency of Mtwo, Race and Medin Nickel-Titanium (NiTi) rotary instruments. Materials and Methods: Sixty mandibular molar mesial roots were selected with angle curvatures between 25-35 degrees and divided into three groups; each containing 20 teeth. Canals were prepared with the rotary files and irrigated with 2.5% NaOCl solution after each instrument. Total of 5mL of normal saline was used as the final rinse; subsequently the canals were dried with paper points. The amount of debris and smear layer in three parts of the root canal walls was evaluated using SEM and the data were analyzed by using the Kruskal-Wallis test and the Mann-Whitney U test. Results: The results for remnant debris in the coronal part of root canals were similar, whereas in the middle third, Mtwo instruments achieved significantly better results compared to Race and Medin instruments. In the apical third of the root canals more debris was created by Race instruments. Conclusion: Overall, Mtwo instruments had greater success in producing clean canals.